2018
DOI: 10.3390/su10113925
|View full text |Cite
|
Sign up to set email alerts
|

Roadway Lighting Retrofit: Environmental and Economic Impact of Greenhouse Gases Footprint Reduction

Abstract: Roadway lighting retrofit is a process continuously developed in urban environments due to both installation aging and technical upgrades. The spectacular example is replacing the high intensity discharge (HID) lamps, usually high pressure sodium (HPS) ones, with the sources based on light-emitting diodes (LED). The main focus in the related research was put on energy efficiency of installations and corresponding financial benefits. In this work, we extend those considerations analyzing how lighting optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Improving the energy efficiency of exterior lighting requires consideration of several areas, from the planning process to the user end phase. A great deal of research has been conducted with a focus on energy and exterior lighting-e.g., light sources [27,28], intelligent and smart systems [29,30], control systems [31], dimming [32,33], optimization [34][35][36], quality needs [37,38], energy performance indicators [39][40][41], and evaluations [1,[42][43][44]. Other studies have examined combinations of factors, e.g., a change of light source and dimming [45].…”
Section: Energy Performance Of Exterior Lightingmentioning
confidence: 99%
“…Improving the energy efficiency of exterior lighting requires consideration of several areas, from the planning process to the user end phase. A great deal of research has been conducted with a focus on energy and exterior lighting-e.g., light sources [27,28], intelligent and smart systems [29,30], control systems [31], dimming [32,33], optimization [34][35][36], quality needs [37,38], energy performance indicators [39][40][41], and evaluations [1,[42][43][44]. Other studies have examined combinations of factors, e.g., a change of light source and dimming [45].…”
Section: Energy Performance Of Exterior Lightingmentioning
confidence: 99%
“…For the tested LED luminaires, the harmonic deformation on the supply voltage, with higher values but still within the standard limits, will cause an increase in the current harmonic distortion generated by the LED luminaires. Different studies [18][19][20] have addressed the possibility of retrofitting existing luminaires with LEDs with the purpose of reducing waste materials and reusing different components of the existing luminaires. It was concluded that the selection of the proper lighting gear is crucial during the retrofit design phase, not only for satisfying the requirements imposed by regulations on average illuminance and uniformity but also for their energy performance and power quality [20].…”
Section: Introductionmentioning
confidence: 99%